Crystal structure of di-μ-chlorido-bis[chloridobis(1,2-dimethyl-5-nitro-1H-imidazole-κN (3))copper(II)] acetonitrile disolvate - Quinlivan, Patrick J. (Acta Crystallogr E Crystallogr Commun, 2016)
1,2-Dimethyl-5-nitroimidazole (dimetridazole, dimet) is a compound that belongs to a class of nitroimidazole drugs that are effective at inhibiting the activity of certain parasites and bacteria. However, there are few reports that describe structures of compounds that feature metals complexed by dimet. Therefore, we report here that dimet reacts with CuCl(2)·H(2)O to yield a chloride-bridged copper(II) dimer, [Cu(2)Cl(4)(C(5)H(7)N(3)O(2))(4)] or [Cu(μ-Cl)Cl(dimet)(2)](2). In this molecule, the Cu(II) ions are coordinated in an approximately trigonal–bipyramidal manner, and the molecule lies across an inversion center. The dihedral angle between the imidazole rings in the asymmetric unit is 4.28 (7)°. Compared to metronidazole, dimetridazole lacks the hydroxyethyl group, and thus cannot form intermolecular O⋯H hydrogen-bonding interactions. Instead, [Cu(μ-Cl)Cl(dimet)(2)](2) exhibits weak intermolecular interactions between the hydrogen atoms of C—H groups and (i) oxygen in the nitro groups, and (ii) the terminal and bridging chloride ligands. The unit cell contains four disordered acetonitrile molecules. These were modeled as providing a diffuse contribution to the overall scattering by SQUEEZE [Spek (2015 ▸). Acta Cryst. C71, 9–18], which identified two voids, each with a volume of 163 Å(3) and a count of 46 electrons, indicative of a total of four acetonitrile molecules. These acetonitrile molecules are included in the chemical formula to give the expected calculated density and F(000).